O CUIDADO DE SI DE IDOSOS QUE CONVIVEM COM CÂNCER EM TRATAMENTO AMBULATORIAL - Lucimara Sonaglio Rocha; Margrid Beuter; Eliane Tatsch Neves; Marinês Tambara Leite; Cecília Maria Brondani; Nara Marilene Oliveira Girardon Perlini (Universidade Federal de Santa Catarina, Programa de Pós Graduação em Enfermagem, 2014)
This is a qualitative descriptive study with the aim to analyze the self-care of elderly cancer patients undergoing outpatient treatment, from the perspective of their autonomy. Fifteen elderly individuals undergoing treatment in a blood-oncology outpatient center of a university hospital participated in the research. Data were collected with semi-structured interviews conducted in 2010. Independence and ability for self-care by the elderly patients were evaluated using the Katz and Lawton scales. The data collected were submitted to thematic analysis. Four categories were identified: manifestations of self-care of elderly cancer patients; care in the family and its dynamics; adaptation to the limitations of the disease; and living with finiteness. In conclusion, the autonomy for self-care of the elderly patients is manifested in the concern with diet, knowing their bodies' limits, the changes imposed by living with cancer and family support.